Spatial and Social Mobility - Borck, Rainald; Wrede, Matthias (Journal of Regional Science, 2018)
This paper analyzes the relationship between spatial mobility and socialmobility. It develops a two-skill-type spatial equilibrium model of two regions with location preferences where each region consists of an urban area that is home to workplaces and residences and an exclusively residential suburban area. The paper demonstrates that relative regional social mobility is negatively correlated with segregation and inequality. In the model, segregation, income inequality, and socialmobility are driven by differences between urban and residential areas in commuting cost differences between high-skilled and low-skilled workers, and also by the magnitude of taste heterogeneit
Keywords: inequality; segregation; social mobility; spatial mobility